Brunei Darussalam : Report on External Sector Statistics Mission (Remote) (July 26-29, 2020). - International Monetary Fund. Statistics Dept. (Washington, D.C. : International Monetary Fund, 2022)
An External Sector Statistics (ESS) technical assistance (TA) mission was conducted remotely to Brunei Darussalam, during July 26-29, 2020, aimed at improving the quality of ESS, in line with the authoritiesa' request. This is the most recent TA mission on ESS to Brunei Darussalam following a previous one that took place more than 16 years ago by the IMF's Statistics Department.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet
Keywords: International Agreements and Observance; International Organizations; Monetary Policy; Brunei Darussalam